A CASE METHOD–BASED MATHEMATICS MODULE INTEGRATING EAST NUSA TENGGARA ETHNOMATHEMATICS FOR NUMERACY LITERACY - Nur Hasanah Syarief; Reschi Vanchristo Ardi Sinlae (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Improving students' numeracy literacy requires mathematics learning that is contextual, meaningful, and connected to students' cultural experiences. This study aimed to develop a case method–based mathematics learning module integrating East Nusa Tenggara ethnomathematics to improve students' numeracy literacy. The study employed a Research and Development (R&D) approach using the ADDIE model. The module was validated by two subject-matter experts and two media experts, while its practicality was evaluated through teacher and student response questionnaires. Its effectiveness was examined using a one-group pre-test–post-test design, analyzed with a paired-samples t-test and Cohen's d effect size. The subject-matter experts assigned validation scores of 4.6 for content accuracy, 4,8 for ethnomathematics content, 4,7 for instructional strategy, and 3,9 for language, indicating that module was valid to very valid. The media experts assigned scores of 4,4 for visual design, 4,3 for layout, and 4,9 for usability, indicating that the module was very valid. The practicality evaluation yielded scores of 89% for attractiveness, 86% for ease of use, and 88% for both module quality and user guidance, indicating that the module was highly practical. Students' numeracy literacy improved significantly after the implementation of the module (p=0.007), with the mean score increasing from 69,63 to 85,25. The module demonstrated a medium effect size (Cohen's d=0.683), indicating that the improvement was not only statistically significant but also educationally meaningful. These findings indicate that the developed module is a valid, practical, and effective learning resource for improving students' numeracy literacy while fostering appreciation of local cultural values.